Penicillin Allergy and Perioperative Anaphylaxis - Ramsey, Allison (Frontiers in Allergy, 2022)
Penicillin allergy is the most commonly reported drug allergy, while perioperative anaphylaxis is overall rare. This review covers the epidemiology of both penicillin allergy and perioperative anaphylaxis both separately and taken together. Considerations regarding anaphylaxis to penicillin during pregnancy are also discussed, since penicillin is the drug of choice for Group B Streptococcus prophylaxis. The minimal cross reactivity between penicillins and cephalosporins is addressed, since the vast majority of patients with a penicillin allergy label can receive perioperative cephalosporins. The management of the patient who has experienced perioperative anaphylaxis, including the importance of allergy referral is covered. Approaches to pre-operative penicillin allergy evaluations and opportunities for education are highlighted.